Care Pathways in a Suicide Crisis Assessment Nurse (SCAN) service. Issue 1 (20th November 2019) - Raymond, Cora; Myers, Susan; Daly, Robert; Murray, Declan; Lyne, John
Abstract: Aim: The Suicide Crisis Assessment Nurse service has been developed as a Primary Care suicide intervention over the last decade. The current study aimed to describe the demographic details of users of this nurse led service, and to evaluate subsequent care pathways following this intervention. Methods: This study was conducted using a retrospective file review with a cross‐sectional observational design investigating demographic details of service users and care pathways in a Suicide Crisis Assessment Nurse service within a defined catchment area of Ireland between June 2015 and May 2017. Results: The majority of referrals were managed in Primary Care following Suicide Crisis Assessment Nurse intervention. There was an increase in Primary Care management pathway in the second year of the service which was independent of age and gender. Conclusion: There was an increase in referrals to the service over time, and the majority of presentations were managed in primary care following Suicide Crisis Assessment Nurse intervention. The study suggests that primary care interventions for suicidal crises merit further research. SUMMARY STATEMENT: What is already known about this topic? Suicide Crisis Assessment Nurse service has been developed as a suicide intervention over the last decade. The service aims to provide rapid assessment of suicidality at Primary Care level. There is limited evaluation of care pathways in the Suicide Crisis Assessment Nurse service to date. What this paper adds? This paper evaluates care pathways in a Suicide Crisis Assessment Nurse service which have not been investigated previously. The paper found that the majority of referrals to the Suicide Crisis Assessment Nurse service continue management in Primary Care after referral and assessment. The implications of this paper: This paper highlights the value of a SCAN service in managing suicidality in a Primary Care setting. Further studies are needed to evaluate the SCAN model to investigate other outcomes such as subsequent self‐harm and later care pathways in mental health services.